Manajemen Komunikasi antara PT Astra Honda Motor dan Dinas Pendidikan Kota Yogyakarta dalam Penerapan Program Corporate Social Responsibility (Studi Kasus: Penerapan Program CSR Kurikulum Etika Berlalu Lintas Tingkat SMP hingga SMA yang Dilakukan PT AHM di Kota Yogyakarta) - IRAWAN, GUSTI IRAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
PT Astra Honda Motor which gives a big attention to education sector in Indonesia triggers CSR program “Traffic Ethics Curriculum” (Kurikulum Etika Berlalu Lintas) accompanied by corporation’s concern to decrease potency of traffic accident which happen to motorcyclist. PT AHM asks some government agencies, especially Education Office of Yogyakarta City, as the external party to cooperate in the CSR program. The implementation of the program is embodied in form of building and socialization about traffic ethics which is targeted in education sector, for the students as early as possible, whether as highway users or the next motorcyclist. This study aims to analyze communication management between PT AHM and Yogyakarta City Education Office in implementing CSR program Kurikulum Etika Berlalu Lintas in Junior and Senior High School level in Yogyakarta city. The subjects of this research are PT AHM and Yogyakarta City of Education Office in collaborative relation to implement CSR program of AHM which is held in Yogyakarta city. The object of the research is communication management between AHM and Yogyakarta City Education Office in implementing CSR program in education sector Kurikulum Etika Berlalu Lintas. This research is qualitative research which uses case study method. Interview and direct observation used to get conformity of data between informant and the object of the research. The results showed that the collaboration of both sides is a collaborative design in a model of communicating strategic CSR program. The collaborative relation explained that a corporation needs to involve other party outside of the corporation itself, especially government agencies so that the CSR program can run effectively. This collaboration depicted that there is also process of planning, organizing and actuating of the program which is related to communication elements in implementing of CSR program.